Protein nanorings organized by poly(styrene-block-ethylene oxide) self-assembled thin films. Issue 47 (26th October 2015) - Malmström, Jenny; Wason, Akshita; Roache, Fergus; Yewdall, N. Amy; Radjainia, Mazdak; Wei, Shanghai; Higgins, Michael J.; Williams, David E.; Gerrard, Juliet A.; Travas-Sejdic, Jadranka
Abstract : Illustration of the sample preparation process. Lsmα (top left) is mixed with PS- b -PEO (top right) and spin coated into thin films with the protein sequestered into the PEO domains. Abstract : This study explores the use of block copolymer self-assembly to organize Lsmα, a protein which forms stable doughnut-shaped heptameric structures. Here, we have explored the idea that 2-D crystalline arrays of protein filaments can be prepared by stacking doughnut shaped Lsmα protein into the poly(ethylene oxide) blocks of a hexagonal microphase-separated polystyrene- b -polyethylene oxide (PS- b -PEO) block copolymer. We were able to demonstrate the coordinated assembly of such a complex hierarchical nanostructure. The key to success was the choice of solvent systems and protein functionalization that achieved sufficient compatibility whilst still promoting assembly. Unambiguous characterisation of these structures is difficult; however AFM and TEM measurements confirmed that the protein was sequestered into the PEO blocks. The use of a protein that assembles into stackable doughnuts offers the possibility of assembling nanoscale optical, magnetic and electronic structures.